2009
DOI: 10.1111/j.1365-2729.2008.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining student satisfaction with wholly online learning

Abstract: Learner satisfaction has been shown to be positively correlated with quality of learning outcomes. An understanding of the factors that influence student satisfaction with online learning in a particular context can be used as an input to the appropriate design of learning environments, and for the provision of targeted support to students, with an aim to positively influence the student online learning experience. Following the mandatory inclusion of at least one wholly online unit of study in all undergradua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
23

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 29 publications
(35 reference statements)
5
90
0
23
Order By: Relevance
“…The findings of this research suggest that the form of assessment used in an AOD may be less important than the fact that assessment of some kind is included given the positive outcomes that have been found to be associated with assessing AOD (Dennen, 2008;Klisc et al, 2009;Palmer & Holt, 2009). Significant improvements in students' levels of perceived critical thinking occurred for students who had their AOD contributions assessed, as well as for those who had a post-AOD assessment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The findings of this research suggest that the form of assessment used in an AOD may be less important than the fact that assessment of some kind is included given the positive outcomes that have been found to be associated with assessing AOD (Dennen, 2008;Klisc et al, 2009;Palmer & Holt, 2009). Significant improvements in students' levels of perceived critical thinking occurred for students who had their AOD contributions assessed, as well as for those who had a post-AOD assessment.…”
Section: Discussionmentioning
confidence: 94%
“…Summative assessment has been claimed both to motivate students to participate in the online discussion and to take extra care in creating their discussion contributions (Hara et al, 2000;Palmer & Holt, 2009). Using assessment in an AOD encourages more involvement in the discussion, which in turn fosters critical thinking in students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies find high levels of student satisfaction with the interactive components of online courses and others find high levels of dissatisfaction with interactive components, leading students to complain about feelings of isolation . Palmer and Holt (2009) While the research on interaction and satisfaction is inconclusive, educators would be remiss if they dismissed the importance of student interaction in online courses. Research has shown that one way to increase interaction is to provide flexible support through online tutoring (Fischer et al 2003).…”
Section: Online Learning Literature Reviewmentioning
confidence: 99%
“…There is a positive relationship between student satisfaction and the quality of teaching (Palmer and Holt, 2009). Five dimensions of online education are determined as educational effectiveness, cost effectiveness, accessibility, instructor and student satisfaction (Simsek, 2012).…”
Section: Student Satisfaction In Distance Educationmentioning
confidence: 99%